Проектные работы в преподавании английского языка - Akshalova, B. N.; Tashenova, A. S. (Journal of actual problems of jurisprudence, 2019)
This article highlights the issue of using project work in teaching English. The objectives of the given article to highlight the importance of project work in teaching English, to describe its main peculiarities and types, to discover how it influences the students during the educational process and if it helps to learn the language. The given article begins by examining the leading role of using project work as one of the best method in teaching FL. The fundamental researches in the given field were carried out by such prominent scientists and methodologists as Legutke M., Thomas H., Heines S., Brumfit C., Hutchinson T., Fried-Booth D. and others. Working on this article we can make the next conclusion - project work has more positive sides than negative and is effective during the educational process. Students are likely to learn the language with the help of projects and have more fun.